2023
DOI: 10.1002/tqem.21981
|View full text |Cite
|
Sign up to set email alerts
|

Critical review for the quantification of leachate production: Evaluation example for the “Oum Azza” public landfill in Rabat city, Morocco

Abstract: The estimation of leachate quantities produced in landfills is necessary to dimension the treatment plants allowing to reduce the polluting load of these effluents and consequently avoid their negative impacts on the environment. Different leachate quantification methods were used in this study to assess the leachate volume produced at the Oum Azza landfill. The water balance method give comparable estimations of leachate production to the Ouled Berjal landfill ratio. The first method showed average values bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Technological innovation is a key driver of research in the field of biogas potential assessment, with ongoing efforts to optimize biogas production processes, enhance process efficiency, and develop novel biogas upgrading technologies. Advances in digester design, substrate pretreatment methods, and biogas purification techniques are enabling the expansion of biogas production and utilization [56] ( Bouyakhsass et al, 2023). Policy frameworks and regulatory mechanisms governing biogas production and utilization are also significant themes in the literature, with research focusing on the role of government incentives, subsidies, and renewable energy targets in driving renewable energy adoption and promoting sustainable development.…”
Section: Core Themes and Emerging Trendsmentioning
confidence: 99%
“…Technological innovation is a key driver of research in the field of biogas potential assessment, with ongoing efforts to optimize biogas production processes, enhance process efficiency, and develop novel biogas upgrading technologies. Advances in digester design, substrate pretreatment methods, and biogas purification techniques are enabling the expansion of biogas production and utilization [56] ( Bouyakhsass et al, 2023). Policy frameworks and regulatory mechanisms governing biogas production and utilization are also significant themes in the literature, with research focusing on the role of government incentives, subsidies, and renewable energy targets in driving renewable energy adoption and promoting sustainable development.…”
Section: Core Themes and Emerging Trendsmentioning
confidence: 99%
“…As shown in Figure 6b, the turbidity was set at 12.5 mg/L, and the influence of different pH and PAC dosage on turbidity removal was oval, indicating that the interaction between pH and PAC dosage was obvious. Bouyakhsass et al found that the interactions between coagulant dose and pH have a significant effect on turbidity reduction [44]. When the dosage was 18.84~28.84 mg/L and the pH was 7.2~8.4, the residual turbidity after coagulation was low.…”
Section: Response Surface Analysismentioning
confidence: 99%